2010
DOI: 10.1186/1758-2652-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV‐1 viral subtype on disease progression and response to antiretroviral therapy

Abstract: BackgroundOur intention was to compare the rate of immunological progression prior to antiretroviral therapy (ART) and the virological response to ART in patients infected with subtype B and four non-B HIV-1 subtypes (A, C, D and the circulating recombinant form, CRF02-AG) in an ethnically diverse population of HIV-1-infected patients in south London.MethodsA random sample of 861 HIV-1-infected patients attending HIV clinics at King's and St Thomas' hospitals' were subtyped using an in-house enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
106
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 50 publications
15
106
3
4
Order By: Relevance
“…In this study, some viral and host characteristics of HIV/viral hepatitis-coinfected patients were evaluated in order to gain further knowledge about this issue. Furthermore, the results of the present study are in accord with previous investigations, that most HIV-1 subclade F1 strains circulating in Brazil may contain recombinant genomes 16 .…”
Section: Discussionsupporting
confidence: 82%
“…In this study, some viral and host characteristics of HIV/viral hepatitis-coinfected patients were evaluated in order to gain further knowledge about this issue. Furthermore, the results of the present study are in accord with previous investigations, that most HIV-1 subclade F1 strains circulating in Brazil may contain recombinant genomes 16 .…”
Section: Discussionsupporting
confidence: 82%
“…There is also evidence that recombinant forms have a higher rate of progression to AIDS than does subtype A (10,14), although this was not observed in another study (12). There are conflicting reports regarding the rate of disease progression of subtype C relative to that of other subtypes (12,(15)(16)(17)(18). While there is general agreement that subtype C has a transmissibility rate at least equal to those of other M group subtypes (19,20), some studies have reported increased transmissibility of subtype C compared to subtypes A and D (21)(22)(23).…”
mentioning
confidence: 79%
“…However, a more extensive survey would be needed to establish an influence of G153 on clade D or CRF02_AG envelopes. Of note, clade D viruses have been associated with faster disease progression (1,14,19,20,45) and a higher frequency of dementia (40). In addition, CXCR4 tropism was common among CRF02_AG viruses, a sign of a mature HIV epidemic (15).…”
Section: Discussionmentioning
confidence: 99%